2003
DOI: 10.1074/jbc.m210627200
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Family 3 Glycoside Hydrolases from Barley with α-l-Arabinofuranosidase and β-d-Xylosidase Activity

Abstract: An ␣-L-arabinofuranosidase and a ␤-D-xylosidase, designated ARA-I and XYL, respectively, have been purified about 1,000-fold from extracts of 5-day-old barley (Hordeum vulgare L.) seedlings using ammonium sulfate fractional precipitation, ion exchange chromatography, chromatofocusing, and size-exclusion chromatography. The ARA-I has an apparent molecular mass of 67 kDa and an isoelectric point of 5.5, and its catalytic efficiency during hydrolysis of 4-nitrophenyl ␣-L-arabinofuranoside is only slightly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 64 publications
10
122
0
5
Order By: Relevance
“…Similarly, numerous enzymes in glycoside hydrolase family 3, such as α-L-arabinofuranosidase from barley (Hordeum vulgare L.) and β-xylosidase from A. japonicas, have been characterized as bifunctional enzymes having both α-L-arabinofuranosidase and β-D-xylopyranosidase activities. 24,29) P1.2, which was identified as a β-glucosidase, showed slightly higher efficiency toward laminaribiose than pNP-Glc and about 24-fold higher than cellobiose, suggesting its preference for the β-1,3 over the β-1,4 glucosidic bond. Nonetheless, among the three enzymes obtained in this study, P1.2 appeared the most efficient in hydrolysis of tested natural disaccharides, cellobiose, and laminaribiose.…”
Section: Determination Of Optimal Reaction Conditions and Stability Omentioning
confidence: 99%
“…Similarly, numerous enzymes in glycoside hydrolase family 3, such as α-L-arabinofuranosidase from barley (Hordeum vulgare L.) and β-xylosidase from A. japonicas, have been characterized as bifunctional enzymes having both α-L-arabinofuranosidase and β-D-xylopyranosidase activities. 24,29) P1.2, which was identified as a β-glucosidase, showed slightly higher efficiency toward laminaribiose than pNP-Glc and about 24-fold higher than cellobiose, suggesting its preference for the β-1,3 over the β-1,4 glucosidic bond. Nonetheless, among the three enzymes obtained in this study, P1.2 appeared the most efficient in hydrolysis of tested natural disaccharides, cellobiose, and laminaribiose.…”
Section: Determination Of Optimal Reaction Conditions and Stability Omentioning
confidence: 99%
“…However, several enzymes in families 3 and 51 are capable of hydrolyzing both L-Ara and D-Xyl from a variety of substrates in vitro and therefore may be considered as bifunctional arabinofuranosidase/b-D-xylosidase (xylosidase; EC 3.2.1.37) enzymes. For example, when considering barley (Hordeum vulgare) ARA-I, Arabidopsis XYL3 and ARAF1, and alfalfa (Medicago sativa) MsXyl1, the k cat /K m ratio using artificial substrates such as 4-nitrophenyl-a-L-arabinofuranose (pNPA) and 4-nitrophenyl-b-D-xylopyranose are of the same order of magnitude, suggesting that they are true bifunctional enzymes (Lee et al, 2003;Minic et al, 2004Minic et al, , 2006Xiong et al, 2007). The hydrolytic activity of many of these enzymes has also been tested with natural polysaccharidic substrates.…”
mentioning
confidence: 99%
“…2). Lee et al (2003) purified a new α-L-arabinofuranosidase from monocotyledonous barley and indicated the enzyme belongs to GH family 3. Following barley, family 3 α-L-arabinofuranosidase was purified from Japanese pear, a dicotyledonous plant (Tateishi et al, 2005a).…”
Section: Expression Pattern Of α-L-arabinofuranosidasesmentioning
confidence: 99%
“…Hence, the expression pattern of family 3 α-L-arabinofuranosidase described below was also summarized including β-xylosidase and putative α-L-arabinofuranosidase/β-xylosidase. cDNA clones of the enzymes were isolated from barley (Lee et al, 2003), tomato (Itai et al, 2003), Arabidopsis (Goujon et al, 2003;Minic et al, 2004Minic et al, , 2006, Japanese pear (Tateishi et al, 2005a), radish (Raphanus sativus) (Kotake et al, 2006), peach (Hayama et al, 2006), strawberry (Bustamante et al, 2006), and alfalfa (Medicago sativa) (Xiong et al, 2007). They constitute a small gene family and the expression of each isozyme was found in various organs and developmental stages.…”
Section: Expression Pattern Of α-L-arabinofuranosidasesmentioning
confidence: 99%